THE IMPLEMENTATION OF CERGAM AND PERMEN KATA IN LITERACY PROGRAM FOR 1 st GRADE STUDENTS AT POJOKSARI ELEMENTARY SCHOOL DURING “KAMPUS MENGAJAR 5” - Anwar, Taufik Shoqibul; Pratama, Mochamad Rizqi Adhi (Universitas Ngudi Waluyo, 2023)
Application of Permen Kata and cerita gambar learning media in the Kampus Mengajar program to improve literacy skills. The problems in this research include what and how the learning media used are implemented, as well as how teachers prespection. The objective of this researcher is to determine the implementation of learning media and the influence of learning activities. This research was a type of qualitative research, using Case Study techniques. The research results emphasized general meaning and the process used case study research methods, in-depth observation, and interviews. Data will be disclosed by explaining in words clearly and in detail. The material taught to improve reading skills can be seen through the use of media to improve reading skills, and both use cooperative learning techniques. with a scientific and inquiry learning approach. Students feel happy with use learning media. The learning media used received a good response from children.